1333. Developing an Educational Tool to Improve Housestaff Knowledge, Attitudes, and Behavior in Managing Common Infectious Diseases. (26th November 2018) - Jacob, Paul; Person, Anna; Bloch, Karen; Fiske, Christina T; Kuriakose, Kevin; Bourgi, Kassem; Dougherty, David; Dobrzynski, David; Staub, Milner Owens; Byrge, Kelly; Grome, Heather; Cohen, Caroline; et al.
Abstract: Background: Improving internal medicine (IM) trainees skills in managing common infectious diseases is essential to their development as competent physicians. We currently lack quantitative data of the knowledge and attitudes of IM housestaff regarding their management of common infectious diseases. We applied the knowledge, attitude, and behavior model to a pre-intervention survey aimed to uncover housestaff knowledge gaps and discomfort in managing several of the most commonly encountered infectious diseases at our institution. Using this information, we plan to develop a targeted post-survey intervention to increase self-efficacy and improve antimicrobial prescription practices among trainees. Methods: Survey questions were based on Infectious Disease Society of America (IDSA) guidelines and developed using an iterative process involving interviews of infectious disease physicians and IM housestaff. We chose to focus on cystitis, pneumonia, and skin and soft-tissue infections. The anonymous survey tool was developed using a secure, online platform, and distributed in January 2018. Participation was voluntary and no remuneration for participation was offered. Results: Out of 165 survey recipients, 50 trainees (30%) responded. Fifty-eight percent of trainees stated that they possessed only an average level of knowledge regarding the management of cystitis, pneumonia, and cellulitis. While 98% of housestaff confirmed that they utilized additional resources for information, only 24% felt routinely comfortable making decisions without an infectious disease consultation. Ninety-six percent of trainees felt that an institution-specific guide describing the management of common infectious diseases would be highly beneficial. Conclusion: Trainees still lack the knowledge and confidence to make decisions regarding the empiric management of cystitis, pneumonia, and skin and soft-tissue infections at our academic medical center. There is a strong desire for an institution-specific educational resource to provide guidance for these decisions. Increasing trainee self-efficacy and improving their antimicrobial prescription practice patterns should be an educational priority. Disclosures: All authors: No reported disclosures.